Evaluating Malaysian Islamic banks’ service quality: an importance-performance analysis approach - Mohd Thas Thaker, Hassanudin; Khaliq, Ahmad; Mohd Thas Thaker, Mohamed Asmy (2015)
This study was designed to evaluate the service quality of Malaysian Islamic Banking from the customers’ perspectives. The primary data was collected by administering survey questions in Klang Valley (Selangor and Kuala Lumpur) and the analysis was conducted using the Importance-Performance Analysis (IPA). The results revealed that service quality attributes such as Shariah requirements, reliability, assurance, responsiveness, website efficiency, and tangibility play an important role in determining customer satisfaction in Malaysian Islamic banks. The outcome of these findings should assist market players, particularly the Malaysian Islamic Banking industry, and policy makers in understanding and enhancing customer satisfaction regarding the quality of service offered by the Islamic Banking industry in Malaysia. The research findings could also be used as part of the blueprints for market players to draft the necessary policies with regard to service quality of the mentioned industry.